Daya Hasil 15 Galur Cabai IPB dan Ketahanannya terhadap Penyakit Antraknosa yang Disebabkan oleh Colletotrichum acutatum - Lia Marliyanti; Muhamad Syukur; . Widodo (Departemen Agronomi dan Hortikultura, 2013)
This research intended to evaluate the yield of 15 IPB chili pepper lines from Plant Genetics and Breeding Division, Department of Agronomy and Horticulture, IPB, and was compared then with 5 commercial varieties. This research also intended to evaluate its resistance to anthracnose. This research was done from January until July 2011 at Bogor. The main character that evaluated was yield component and resistant to character. IPB019015, IPB110005, IPB120005, IPB009019, IPB002046, and IPB001004 had yield ability better than commercial varieties. IPB019015 had resistance to anthracnose disease better than commercial varieties.Keywords: anthracnose, chili, yield component